Effect of erythropoietin as an adjunct to primary percutaneous coronary intervention: a randomised controlled clinical trial. Issue 19 (7th September 2011) - Ludman, Andrew J; Yellon, Derek M; Hasleton, Jonathan; Ariti, Cono; Babu, Girish Ganesha; Boston-Griffiths, Edney; Venugopal, Vinod; Walker, Malcolm; Holdright, Diana; Swanton, Howard; Crake, Tom; Brull, David; et al.
Abstract : Objective: The acute administration of high-dose erythropoietin (EPO) on reperfusing ischaemic myocardium has been reported to halve myocardial infarct (MI) size in preclinical studies, but its effect in ST elevation myocardial infarction patients undergoing primary percutaneous coronary intervention (PPCI) remains unknown. We investigated whether high-dose EPO administered as an adjunct to PPCI reduces MI size. Design: Double-blinded, randomised, placebo-controlled. Setting: Single tertiary cardiac centre. Patients: Fifty-one ST elevation myocardial infarction patients undergoing PPCI. Interventions: Patients were randomly assigned to receive either a single intravenous bolus of EPO (50 000 IU) prior to PPCI with a further bolus given 24 h later (n=26) or placebo (n=25). Main outcome measures: MI size measured by 24 h area under the curve troponin T and cardiac magnetic resonance imaging performed on day 2 and at 4 months. Results: EPO treatment failed to reduce MI size (troponin T area under the curve: 114.6±78 μg/ml EPO vs 100.8±68 μg/ml placebo; infarct mass by cardiac magnetic resonance: 33±16 g EPO vs 25±16 g placebo; both p>0.05). Unexpectedly, EPO treatment doubled the incidence of microvascular obstruction (82% EPO vs 47% placebo; p=0.02) and significantly increased indexed left ventricular (LV) end-diastolic volumes (84±10 ml/m 2 EPO vs 73±13 ml/m 2 placebo; p=0.003), indexed LV end-systolic volumes (41±9 ml/m 2 EPO vs 35±11 ml/m 2 placebo; p=0.035) and indexed myocardial mass (89±16 g/m 2 EPO vs 79±11 g/m 2 placebo; p=0.03). At 4 months, there were no significant differences between groups. Conclusions: High-dose EPO administered as an adjunct to PPCI failed to reduce MI size. In fact, EPO treatment was associated with an increased incidence of microvascular obstruction, LV dilatation and increased LV mass. Clinical Trial Registration Information: http://public.ukcrn.org.uk/search/StudyDetail.aspx?StudyID=4058 Unique Identifier=Study ID 4058.